THE RELATIONSHIP BETWEEN PSYCHOLOGICAL STABILITY AND ACADEMIC SUCCESS - Sa'dullayeva Dano Abdukomil qizi (Ecominds Press, 2025)
The article reveals the concept of psychological stability in modern psychology and the issue of its application in science, the opinions of scientists, scientific research.